Kinetic behaviour and thermodynamic study of peanut oil extraction using ultrasound technology / Nur Shahidah Musa - Musa, Nur Shahidah (2019)
In the present study, ultrasound assisted extraction was utilized to extract oil from peanut. There are four type of main operating parameter such as type of solvents, extraction time, extraction temperature and solvent to solid ratio were investigated. The optimum conditions were found at 15 min reaction time, extraction temperature of 40oC, solvent to solid ratio of 20:1 and ethyl acetate as solvent. While, the maximum oil yield is 43.8%. Evaluation of kinetics of oil extraction process was done by using hyperbolic model. High values of coefficient of determination (R2 ≥ 0.9515) and low values of the mean relative percentage deviation (MRPD ≤ 0.2759) were obtained, showing the model used were suitable to describe the kinetic of peanut oil extraction. Furthermore, the influence of two parameter of extraction which are extraction temperature and solvent to solid ratio on oil yield were studied. It was found that the oil yield increased with increasing of extraction temperature and solvent to solid ratio. The activation energy (Ea) was calculated as 13.402 kJ mol−1 and the extraction of peanut oil was an endothermic process.